Histamine increases the level of IFNγ produced by HIV-1 specific CTLs and this production depends on total IgE level - Hanzlikova, J; Sedlacek, D; Liska, M; Gorcikova, J; Vlas, T; Amiramini, S; Panzner, P; Maly, M (Journal of immunological methods, 2012)
BACKGROUND: The HIV (human immunodeficiency virus) population remains a global concern whose treatment is effective, though not yet optimal. Immune based therapies have thus far been disappointing and still need to be explored further. Based on published data suggesting that the functions of cytotoxic CD8+ T lymphocytes (CTL) can be improved by histamine, we investigated the effect of histamine in vitro on HIV-1 specific CD8+ T lymphocytes in HIV+ subjects. RESULTS: 60 HIV+ subjects were included in the study. We evaluated CTL function by IFNγ (interferon gamma) production (using the enzyme-linked immunospot assay (Elispot), BD Bioscience). Changes in the production of IFNγ after incubation with histamine were compared with the levels of total IgE (immunoglobulin E, measured using a Dade Behring analyzer), because histamine is endogenously released through IgE. Activation of HIV-specific CTL by histamine occurs via H2R (histamine receptors). Thus we attempted to block this activation using cimetidine (antagonist H2R). CONCLUSIONS: We found an increase in IFNγ production after the activation of HIV-1 specific CD8+ T lymphocytes by histamine (this elevation was blocked by cimetidine), furthermore, we demonstrated a negative correlation between the production of IFNγ and levels of total IgE.
Keywords: HIV Infections; imunoglobulin E; HIV infekce; Humans; lidé; HIV-1; Histamine; histamin; CD8-Positive T-Lymphocytes; CD8-pozitivní T-lymfocyty; Immunoglobulin E; Interferon-gamma; interferon gama